2014
DOI: 10.1186/1472-6963-14-277
|View full text |Cite
|
Sign up to set email alerts
|

A case study of outsourced primary healthcare services in Sindh, Pakistan: is this a real reform?

Abstract: BackgroundSince a decade, low and middle income countries have a rising trend of contracting their primary healthcare services to NGOs. In Pakistan, public sector often lacks capacity to effectively & equitably manage the healthcare services. It led the government to outsource the administration of primary health care services to a semi-autonomous government entity i.e. Peoples’ Primary Healthcare Initiative (PPHI). This small scale study has assessed the quality of healthcare services at the contracted Basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…However, the reported condition of laboratory capacity by this study is much better than our results i.e. presence of haemoglobin reagent and blood sugar strips 13% and 39% respectively which is 3% and 14% higher than our results [19].The results of our study are also similar to the findings of another study that also reported poor performance of basic health units under district government but the condition of essential medicines shown by this study was extremely poorer as compared to our findings [14].In 2012, Nigeria conducted an assessment with help of United States President"s Emergency Plan for AIDS Relief (PEPFAR) and the United States Agency for International Development (USAID) for primary healthcare facilities both in government and private sector to assess availability and readiness of general and specific services including existing HIV services. The survey reported lack of proper funds, irregular budgetary allocation and improper record keeping at primary healthcare facilities [20] which was consistent with our results with the exception of record maintenance which was found to be in order.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the reported condition of laboratory capacity by this study is much better than our results i.e. presence of haemoglobin reagent and blood sugar strips 13% and 39% respectively which is 3% and 14% higher than our results [19].The results of our study are also similar to the findings of another study that also reported poor performance of basic health units under district government but the condition of essential medicines shown by this study was extremely poorer as compared to our findings [14].In 2012, Nigeria conducted an assessment with help of United States President"s Emergency Plan for AIDS Relief (PEPFAR) and the United States Agency for International Development (USAID) for primary healthcare facilities both in government and private sector to assess availability and readiness of general and specific services including existing HIV services. The survey reported lack of proper funds, irregular budgetary allocation and improper record keeping at primary healthcare facilities [20] which was consistent with our results with the exception of record maintenance which was found to be in order.…”
Section: Discussionsupporting
confidence: 78%
“…The absence of staff can distort the services of health facility and confidence of patients to utilize those services [13], this was also deduced in results of this study that percentage of available staff had a significant impact on mean service readiness (pvalue=0.001).The distance from district health office proved to be non-significant (p-value<0.05) in affecting mean service readiness of primary healthcare facilities. Almost half of the administrative heads were male and half of basic health units had female medical officers, but overall there was not any significant difference in readiness of their facilities (p=0.45) which emphasized that administrative powers being exercised by them did not have any disparity Limited hours of services and lack of ambulance at basic health units is responsible for poor utilization [14] but the outcome of this study showed that there was no difference in service readiness for 24/7 basic health units and others (p value=0.08).This study showed a significant impact of number of visits on the service readiness (p-value=0.022). The results were contradictory to the results of secondary data analysis which concluded uncertainty of the impact of supervision on quality of PHC for low-middle income countries [15].…”
mentioning
confidence: 92%
“…This article is based on a qualitative study carried out to explore stakeholder perspectives on PPP in healthcare service delivery in Sindh province of Pakistan including the reasons for adopting such policies, and the barriers for its implementation. Previous studies conducted in Pakistan have compared performance of government administered health facilities with those run by PPP 12,26,27 . Studies have also identified the challenges in the wider policy context for PPP implementation in the healthcare sector in Pakistan 28,29 .However, there is a dearth of research about stakeholder perspectives on factors that act as barriers in implementation of PPP in healthcare service delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Anbori et al developed a six dimensional instrument to assess perceived quality of healthcare services in Yemen (Abnori, Ghani, Yadav, Daher, & Su, 2010). The outsourcing of healthcare services mainly primary healthcare services has resulted significantly improved certain aspects of quality and this approach is likely to achieve an efficient and equitable healthcare provision in developing countries (Tanzil, Zahidie, Ahsan, Kazi, & Shaikh, 2014).…”
Section: Healthcare Quality Servicementioning
confidence: 99%